Health and Gender Inequalities of the COVID-19 Pandemic: Adverse Impacts on Women's Health, Wealth and Social Welfare - Guerrina, Roberta; Borisch, Bettina; Callahan, Leigh F.; Howick, Jeremy; Reginster, Jean-Yves; Mobasheri, Ali (Frontiers in Global Women's Health, 2021)
In this paper we discuss health and gender inequalities associated with the COVID-19 pandemic and highlight its adverse impacts on women’s health, welfare and social standing. The COVID-19 pandemic has exposed the link between socio-economic inequalities and health outcomes, especially in the area of rheumatic and musculoskeletal (RMDs) diseases. Women are more adversely affected by RMDs diseases compared to men. Epidemiological research carried out over several decades has demonstrated the presence of clear gender patterns in the manifestation of musculoskeletal diseases, including osteoarthritis (OA), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), systemic sclerosis (SS) and osteoporosis (OP). The public health measures that have been adopted in relation to COVID-19 will have a particularly detrimental impact on women in the long term precisely because of existing socio-economic structures. Moreover, the prioritisation of urgent care will further compound this effect. COVID-19 has created a condition of ontological insecurity that is becoming increasingly manifested through various chronic diseases and associated comorbidities. RMDs and their impact on mobility and the ability of individuals to be independent, happy and mobile is a key public health challenge in the post-COVID-19 reality and a key part of the ongoing pandemic. There is an urgent need to engage with policymakers to publicise and prioritise this problem and develop viable solutions to address it.